Properties of Arabinoxylans in Frozen Dough Enriched with Wheat Fiber. Issue 2 (17th August 2016) - Adams, Vivian; Ragaee, Sanaa; Goff, H. Douglas; Abdel‐Aal, El‐Sayed M.
Abstract : The global market for frozen bread dough is rising; however, its quality could deteriorate during extended storage. Our previous study indicated that undesirable changes caused by freezing could be reduced by adding arabinoxylan‐rich fiber sources. The present study investigated the changes in arabinoxylan properties of yeasted dough during frozen storage. Dough samples made from refined, whole, and fiber‐enriched (15% either wheat aleurone or bran) flours were stored at –18°C for nine weeks, and structural properties of arabinoxylan were probed during storage. Water‐extractable arabinoxylan (WEAX) content in dough samples increased by about 19–33% during the first three weeks of storage. Prolonged storage of dough (weeks 6 and 9), however, correlated with a decline in WEAX content. Average molecular weight and intrinsic viscosity of WEAX decreased during storage for all frozen dough samples. Arabinose‐to‐xylose ratios also decreased by 11 and 6% for control and composite dough samples, respectively. There was a significant positive correlation ( r = 0.89, P < 0.0001) between WEAX content of dough and bread quality throughout the storage period. The results demonstrated that changes in dough quality during frozen storage were related to changes in the content and structure of WEAX that took place during frozen storage.